2002
DOI: 10.1111/j.1530-0277.2002.tb02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐Induced Cas Tyrosine Phosphorylation and Fyn Kinase Activation in Rat Brain

Abstract: Background: Tyrosine phosphorylation signaling has been reported to be involved in regulatory mechanisms of ethanol-induced modulation of the central nervous system. Methods:We investigated the effect of ethanol administration on tyrosine phosphorylation signaling in rat brain and also examined the possible involvement of Fyn kinase in the process.Results: Immunoprecipitation experiments showed that Crk-associated src substrate (Cas) was tyrosinephosphorylated in response to ethanol administration. Fyn kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nevertheless, in vitro studies showed that p130Cas is required for neurite extension in cerebellar neurons . Further, ethanol-stimulated Fyn-mediated p130Cas phosphorylation has been reported (Nishio and Suzuki, 2002). Once phosphorylated, p130Cas could signal to many different pathways that normally promote growth and not differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in vitro studies showed that p130Cas is required for neurite extension in cerebellar neurons . Further, ethanol-stimulated Fyn-mediated p130Cas phosphorylation has been reported (Nishio and Suzuki, 2002). Once phosphorylated, p130Cas could signal to many different pathways that normally promote growth and not differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…p130Cas and Cas-L transcripts are found in the developing and postnatal brain (Huang et al, 2006;Merrill et al, 2004), and p130Cas localizes to axons in early development and into adulthood in the spinal cord, cerebellum and cerebral cortex (Huang et al, 2006;Liu et al, 2007;Nishio and Suzuki, 2002). We used several antibodies that specifically recognize Cas proteins and examined their patterns of immunostaining in the developing rat spinal cord.…”
Section: Mycmentioning
confidence: 99%
“…Crk family: CrkI, CrkII, CrkL (Burnham et al 1996;Ishino et al 1995;Petruzzelli et al 1996;Sakai et al 1994a;Salgia et al 1996) Nck (Schlaepfer et al 1997) SHP-2 (Prasad et al 2001;Yo et al 2009) c-Src (Shin et al 2004) Serine-rich Domain 14-3-3 (Briknarova et al 2005) Carboxy-terminal domain AIP4 (Feng et al 2004) APC/C, CDH1 (Nourry et al 2004) Bmx/Etk (Abassi et al 2003) NSP family: BCAR3/NSP2, NSP1, CHAT (Gotoh et al 2000;Lu et al 1999;Sakakibara & Hattori 2000) Nephrocystin (Donaldson et al 2000) p130 Cas , HEF1, Id2 (Law et al 1999) p140Cap (Di Stefano et al 2004) PI3K (Li et al 2000) Src family: c-SRC, LCK, LYN, HCK, FYN, YES (Alexandropoulos & Baltimore 1996;Ishino et al 1995;Kanda et al 1999;Nakamoto et al 1996;Nasertorabi et al 2006;Nishio & Suzuki 2002;Pellicena & Miller 2001;Singh et al 2008) Not mapped/ indirect DDR (Shintani et al 2008) ER alpha (Cabodi et al 2004) Grb2 ) Smad3 (Liu et al 2000) …”
Section: Domainmentioning
confidence: 99%
“…The SFKs are comprised of ten members of which c-Src, Lck, Lyn, Hck, Fyn, and Yes phosphorylate the SD of the Cas proteins (Alexandropoulos & Baltimore 1996;Ishino et al 1995;Kanda et al 1999;Nakamoto et al 1996;Nasertorabi et al 2006;Nishio & Suzuki 2002;Pellicena & Miller 2001;Singh et al 2008). In addition to phosphorylating the p130 Cas SD, cSrc binds to phosphorylated tyrosine residues within SD in vitro (Shin et al 2004).…”
Section: The Src-family Tyrosine Kinases (Sfks)mentioning
confidence: 99%